Pharmacognostical Evaluation of Annona squamosa Linn. - Mona Agrawal; Yogesh Agrawal; Prakash Itankar; Arun Patil; Amruta Kelkar; Jayshree Vyas (International Journal of Phytomedicine, 2011)
Annona sqamosa (Annonaceae) is known as sitaphal in Hindi and custard apple in English is an important medicinal plant. It has been used traditionally in diarrhea, dysentery, cold, as abortifacient, insecticidal drug etc., so would be more suitable to evaluate the drug. This paper deals with the detailed pharmacognostic evaluation of the crude drug. Morphoanatomy of the entire plant have been studied with the aim to aid pharmacognostic and taxonomic species identification using WHO recommended physico-chemical determinations and microscopical characters that will provide referential information for checking adulteration. The physico-chemical and histological parameters presented in this paper may be proposed as parameters to establish authenticity of Annona squamosa and can possibly help to differentiate the drug from its other species. Many important diagnostic characters such as bicollateral vascular bundle, paracytic stomata, pitted and spiral vessel, presence of stone cells, starch grains, lignified xylem and phloem will certainly help in identification of drug.